PENGARUH KOMPETENSI DAN MOTIVASI KERJA TERHADAP KINERJA GURU DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING PADA SMK 1 LHOKSUKON - Sari, Pipi Ida; Marbawi, Marbawi; Murhaban, Murhaban (Universitas Malikussaleh, 2019)
Abstract : This study aims to determine the influence of competence and work motivation through organizational commitment and its impact on teacher performance to the vocational high school North Aceh. The data used is primary data by distributing questionnaires to 74 teacher of the vocational high school North Aceh. Data analysis method used is path analysis and processed with the help of Statistical Package for Social Science (SPSS) application program. The result of the research shows that there is influence of competence and work motivation to organization commitment, and there is also influence of competence, work motivatin and organizational commitment toward teacher performance of the vocational high school North Aceh. Furthermore, the results of the study found that organization commitment variables mediate the absolute (full mediation) relationship of competence and work motivation to the teacher performance to the vocational high school North Aceh.Â Keywords : Competence, Work Motivation, Organizational Commitment, andÂ Teacher Performance.Â